Military Spouses' Self- and Partner-Directed Minimization in the Context of Deployment. (3rd July 2019) - Marini, Christina M.; Wadsworth, Shelley MacDermid; Franks, Melissa M.; Wilson, Steven R.; Topp, Dave; Christ, Sharon L.
Abstract: In light of technological advances enabling military couples to communicate throughout deployment, spouses of deployed service members often make decisions about what to share with service members and how to respond to service members' concerns. In doing so, they manage an emotional boundary between service members and their families. This study focused on 2 behaviors military spouses may use when managing this boundary, namely their minimization of (a) their own concerns (i.e., self-directed minimization ) and (b) service members' concerns (i.e., partner-directed minimization ). The purpose of the current study was to identify correlates and consequences of these behaviors. Findings from a longitudinal structural equation model using 3 waves of data from a sample of 154 married military couples in which the husband was a male National Guard soldier indicated that spouses were more likely to minimize both their own—and service members'—concerns when they themselves reported higher levels of depressive symptomology prior to deployment. Spouses' minimization of service members' concerns during deployment, in turn, predicted higher levels of service members' depressive symptomology at reintegration, even after accounting for their initial depressive symptomology and combat exposure. Implications for intervention efforts aimed at promoting individual and couple adjustment to deployment are discussed.